Glocal loves, transnational dating. The virtual search for a mixed partner by spanish men - Roca Girona, Jordi (Revista de Antropología Social, 2011)
This paper deals with the recent and growing phenomenon of heterosexual mixed couples between a Spanish man and a foreign woman. Many topics have been covered by the international scholarly literature, such as the motivations leading to the decision of searching for a couple of these characteristics, or the varied processes of negotiation encountered in the public and private space. Our contribution is based on one of the fundamental aspects of the reality of and important number of mixed couples: the virtual search for a transnational couple through romantic websites and specialized marriage agencies on the Internet, and the subsequent dating period on the virtual space. We discuss topics such as the commodification of intimacy and the novelties and continuities of loves in the cyberspace in relation to conventional dating.
Keywords: Mixed couples; cyberlove; commodification of intimacy; transnational dating; online love relationships